Bernard Shaw's remarkable religion : a faith that fits the facts - Baker, Stuart E. (Stuart Eddy) (Florida Bernard Shaw series., 2002)
In this book on George Bernard Shaw's philosophy of religion, Stuart Baker examines Shaw's insistence that a religion for the contemporary world must be a true guide to daily living, as well as consistent with science. Baker concludes that Shaw was right and presents Shaw's arguments in analytical, logical, and scientific terms. Where previous work on Shaw's religious thought approaches the subject from the point of view of traditional religion, this study approaches his unusual religious ideas on their own terms, which differ from those of either traditional faith or modern atheistic materialism. Baker supports Shaw's contention that his metaphysical principles provide a more solid foundation for ethics and progressive politics than do most alternatives. Baker also endorses Shaw's belief that the scientific principles of rigorousness, logic, and analytical thinking bear out his argument that teleological principles are at work in the world and that the universe can be said to have a will that could be the subject of careful scientific investigation.